PENGARUH DISIPLIN KERJA, EMPOWERMENT DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN SITINJAU LAUT DAN KECAMATAN DANAU KERINCI KABUPATEN KERINCI: NOVA OKTAVIA, ST - NOVA OKTAVIA (LPPM STIA Nusantara Sakti, 2020)
Human resources are part of a progress in science, development and technology. In order to achieve the objectives of an organization within the government environment, good employee performance is needed. A performance can be said to be good if in doing a job get results in accordance with the objectives, both in quality, quantity and time in accordance with predetermined targets and in accordance with established performance standards. This study aims to determine the effect of work discipline, empowerment and job satisfaction on employee performance. The sample used in this study were 68 respondents who were in the office of the district head of Sitinjau Laut and the office of Danau Kerinci. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that work discipline has an effect on and significant on employee performance, empowerment has an effect on and significant on employee performance, job satisfaction has a significant effect on employee performance, work discipline, empowerment and job satisfaction jointly has a significant and significant effect on the performance of employees in the office of the district head of Sitinjau Laut and the office of Danau Kerinci.